THE CALCULATED BETAS, THE DILEMMAS IN THEIR USE AND THE IMPACT ON CAPM - Aguilar Córdova, Alfredo (2017)
The research showed that the calculated betas offer different values depending on the historical series of data selected by the analyst, there are conflicting results with betas of the asset riskier than the market, but when expanding the selection of historical data, betas become less risky than the market in more than 50% of the observed cases. The results confirm what has been pointed out by some researchers in the past, the beta calculated with historical data is not a good approximation to the Beta of the company. The impact of the beta on the Cost of Capital was verified through the CAPM model in the United States because there are multiple betas depending on the historical series of data to be taken. For this purpose, the calculation of the Betas has been made through a linear regression using some companies quoted in the Asian markets through the choice of the Shanghai Composite index, the European one through the choice of the IBEX 35 and the North American index through the Dow Jones Industrial Average, considering for them a daily frequency of income and selecting a historical series of 3 years, 6 months and 3 months.